2002
DOI: 10.1002/hlca.200290012
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereo‐ and Enantioselective Aziridination of α,β‐Unsaturated Amides with Diaziridine and Mechanistic Consideration on Its Stereochemistry

Abstract: Dedicated to Prof. Dieter Seebach on the occasion of his 65th birthday During studies of aziridination of a,b-unsaturated amides with diaziridine, we found that we could prepare both the cis-and trans-aziridinecarboxamides by choosing an appropriately substituted diaziridine. While 3-monosubstituted diaziridine 2 was suitable for the trans-selective aziridination, employment of 3,3-dialkyldiaziridine 1 resulted in the formation of cis-aziridine carboxamides, irrespective of the geometry of the substrate (Schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Previous explorations of nitrogen transfer from oxaziridines and related species have demonstrated reactivity towards olefin aziridination 10 and with strong organometallic nucleophiles, 11 but no examples of C–H insertion have been reported. In contrast, the use of iminium salt catalysts offered a different opportunity ( Scheme 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous explorations of nitrogen transfer from oxaziridines and related species have demonstrated reactivity towards olefin aziridination 10 and with strong organometallic nucleophiles, 11 but no examples of C–H insertion have been reported. In contrast, the use of iminium salt catalysts offered a different opportunity ( Scheme 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…The mixture obtained was stirred at room temperature for 48 h under argon. The methanol was evaporated at low pressure and the residue was purified by chromatography on silica gel (eluant 9:1 chloroform-methanol) to give compound 1 (10.0 g, 88%), mp 85-87°C (in [14] compound 1 was prepared by aziridination of the dimethylamide of acrylic acid in 40% yield). 1 H NMR Spectrum, δ, ppm: 1.40 (1H, br.…”
mentioning
confidence: 99%
“…Subsequently, the same group reported the synthesis of both cis ‐ and trans ‐aziridines from different diaziridines . They found that, whilst 3‐monosubstituted diaziridine 29 was suitable for the trans ‐selective aziridination reaction to afford compound 30 , 3,3‐disubstituted diaziridine 27 resulted in the formation of cis ‐aziridine carboxamides 28 , irrespective of the geometry of the substrate.…”
Section: Nh‐aziridines From Diaziridinesmentioning
confidence: 99%